2016
DOI: 10.1097/j.pain.0000000000000566
|View full text |Cite
|
Sign up to set email alerts
|

Relieving pain using dose-extending placebos: a scoping review

Abstract: Placebos are often used by clinicians, usually deceptively and with little rationale or evidence of benefit, making their use ethically problematic. In contrast with their typical current use, a provocative line of research suggests that placebos can be intentionally exploited to extend analgesic therapeutic effects. Is it possible to extend the effects of drug treatments by interspersing placebos? We reviewed a database of placebo studies, searching for studies that indicate that placebos given after repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 73 publications
0
65
0
4
Order By: Relevance
“…It is also important to emphasize that these recommendations cannot be generalized in a straightforward manner to non-medical contexts, such as psychotherapy [43]. Several relevant areas, such as the promising field of pharmacological conditioning, or predictors of placebo and nocebo effects, were omitted from the survey because, so far, the relevant evidence is only preliminary [1-14, 44-46]. Finally, we did not focus on specific determinants of placebo and nocebo effects, such as cultural, ethnic, neurobiological or personal characteristics of patients, and the specific ethical and philosophical concerns that these factors raise.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to emphasize that these recommendations cannot be generalized in a straightforward manner to non-medical contexts, such as psychotherapy [43]. Several relevant areas, such as the promising field of pharmacological conditioning, or predictors of placebo and nocebo effects, were omitted from the survey because, so far, the relevant evidence is only preliminary [1-14, 44-46]. Finally, we did not focus on specific determinants of placebo and nocebo effects, such as cultural, ethnic, neurobiological or personal characteristics of patients, and the specific ethical and philosophical concerns that these factors raise.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ability to create pharmacological memories with behavioral and neurobiological drug-like effects throughout conditioning points to a potential innovative approach to clinical pain management. Combining drugs and placebos in conditioning paradigms (e.g., a dose-extending placebo regimen) is clinically relevant because it may provide us with strategies to optimize clinical outcomes, while dependence, cost, and other unwanted side effects of opioid and nonopioid therapeutics are minimized (Colloca et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Unlike many other fields of biomedical sciences, the field of placebo analgesia has been led primarily by advances in human research (Colloca & Benedetti, 2005; Colloca, Enck, & DeGrazia, 2016; Wager & Atlas, 2015). Animal studies—that provide critical synergy to human studies—have lagged in this field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a doctor might prescribe a blister pack of painkillers, and tell the patient that it contains both drugs and placebos -but not which pills are which. Earlier this year, Colloca and her colleagues reviewed 22 studies that used similar techniques, covering conditions such as insomnia, autoimmune diseases and pain 9 . They concluded that these approaches have the potential to reduce side effects (although some of these may be conditioned responses, too), limit problems with drug dependency and toxicity, and reduce costs.…”
Section: Learning Nothingmentioning
confidence: 99%